Rancang Bangun Sistem Informasi Manajemen Bimbingan Skripsi Mahasiswa (SIMBISA) Berbasis Web Menggunakan Framework CodeIgniter 4 (Studi Kasus: Prodi Sistem Informasi UNHI) - Putri Pertiwi, Ni Kadek Sri Ayu; Noppi Adi Jaya, I Kadek; Utari Dewi, Ida Ayu (Program Studi Sistem Informasi, Fakultas Teknologi Informasi dan Sains, Universitas Hindu Indonesia, 2026)
The utilization of information technology in academic management continues to evolve to support the efficiency and quality of higher education services. In the Information Systems Study Program at UNHI, the thesis supervision process is still conducted through several separate platforms, such as Google Forms and messaging applications, which leaves room for improvement in terms of effectiveness through a unified system that integrates the entire process. This study aims to design and develop a web-based Thesis Supervision Management Information System (SIMBISA) to facilitate a more structured and efficient supervision process. The system was developed using the waterfall method and the CodeIgniter 4 framework, while system testing was conducted using the blackbox testing method. The development results show that SIMBISA is capable of facilitating the submission of research topics, supervision scheduling, revision uploads, and the submission of proposal and thesis documents in an organized and well-documented manner. In addition, the system provides easy access to information for students and supervisors to monitor supervision progress. Blackbox testing results indicate that all features function according to user needs, making the system effective in supporting a comprehensive and integrated thesis supervision process. With the implementation of SIMBISA, thesis supervision management is expected to become more systematic, accountable, and accessible at any time throughout the process.